Assessment of water allocations using remote sensing and GIS modeling for Indus Basin, Pakistan - Cheema, Muhammad Jehanzeb Masud; Bakhsh, Allah; Mahmood, Talha; Liaqat, Muhammad Usman (International Food Policy Research Institute, 2016)
Water allocations for canal commands are not uniform throughout Pakistan. They vary from 2.5 to 15 cusec (ft3/sec) per 1,000 acres (i.e. 0.18 – 1.1 litre/sec/hectare) for different canal commands. This variability in water allowance (WA) has resulted in low water productivity (kg of yield per m3 of water use), an indicator used to assess efficient water use, especially in command areas having higher water allocations. In this study, satellite imagery was used to estimate crop water use and corresponding water productivity for each canal command area of the Indus Basin Irriga-tion System. Three years were selected for the study and two representative canal commands (Lower Chenab and Muzaffargarh Canal) were selected for detailed analysis and ground truthing. Spatially distributed maps of land use, crop water use, groundwater use and quality, soil and water salinity, and crop yields at a pixel resolution of 250 m (6.25 ha) were prepared and then verified by field surveys. GIS maps of canal water availability/supply were also prepared to account for the volume of water supplied through irrigation. This spatial database was used to evaluate and create maps of water productivity in the different canal commands.